Vittorio Veneto - Torkar, Blaž (Studia Historica Slovenica, 2019)
Based on the study of archival sources and literature, the author analyses the conditions in the Austro-Hungarian Monarchy and on the southwestern front in 1918. This is followed by an analysis of the preparations for and the course of the Italian offensive at Vittorio Veneto which lasted from October 24 to November 4, 1918. The goal of the Italian Armed Forces was to achieve a decisive breakthrough on the front sector Valdobbiadene%Feltre, in the lower part of the Piave river. After initially successes in resisting, the Austro-Hungarian Armed Forces began to fall apart and was forced to withdraw. The Italian victory ended the war on the southwestern front and caused the collapse of the Austro-Hungarian Armed Forces and the signing of an armistice between Italy and Austria-Hungary. The Austro-Hungarian army, then, began to withdraw while the Italian army carefully and slowly followed and occupied all areas promised to them under the London Memorandum.
Keywords: 1918; Austria-Hungary; Avstro-Ogrska; first world war; Italian offensive; Italija; Italy; jugozahodna fronta; ofenziva; Piava; southwestern front; Svetovna vojna 1914-1918; Vittorio Veneto; zgodovina